A method for controlling the directional arrangement of gray cast iron solidification structure by magnetic field

By applying a magnetic field during the directional solidification of gray cast iron, the magnetic crystal anisotropy of graphite and ferrite and the magnetic dipole interaction under the action of the magnetic field, the directional arrangement of the solidification structure of gray cast iron is achieved, solving the problem of difficulty in regulating the solidification structure of gray cast iron in the prior art, and significantly improving the mechanical properties of the material.

CN115584385BActive Publication Date: 2025-04-18SHANGHAI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211104744.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-09
Publication Date
2025-04-18
Estimated Expiration
2042-09-09

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the solidification structure of gray cast iron, resulting in insufficient mechanical properties.

Method used

By applying a magnetic field during the directional solidification process, the magnetic crystal anisotropy of graphite and ferrite interacts with magnetic dipoles under the action of the magnetic field, the orientation arrangement of the solidification structure of gray cast iron is achieved.

Benefits of technology

The orientation arrangement of the solidification structure of gray cast iron is realized, forming slender eutectoid ferrite grains and sheet-like graphite parallel to the direction of the magnetic field, significantly improving the mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115584385B_ABST
    Figure CN115584385B_ABST
Patent Text Reader

Abstract

The present invention provides a method for regulating the directional arrangement of gray cast iron solidification structure by magnetic field, and relates to the technical field of metal material structure regulation. The present invention is based on the magnetocrystalline anisotropy of graphite and ferrite under the action of a magnetic field, and the interaction of magnetic dipoles in ferrite, so as to change the directional solidification structure of gray cast iron. Due to the coupling effect of the magnetocrystalline anisotropy of graphite and the growth characteristics of flake graphite, the application of a magnetic field induces the flake graphite to be regularly arranged parallel to the direction of the magnetic field. Under the action of the magnetic field, the interaction of magnetic dipoles in ferrite and the magnetocrystalline anisotropy of ferrite cause the eutectoid ferrite to change from the randomly distributed equiaxed shape when there is no magnetic field to slender grains arranged parallel to the direction of the magnetic field, and the slender grains parallel to the direction of the magnetic field are arranged parallel to the direction of the magnetic field. <001> The texture components are enhanced. The present invention realizes the regulation of the directional solidification structure of gray cast iron, and solves the problem that other methods cannot realize the directional arrangement of the solidification structure of gray cast iron.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material structure control, and in particular to a method for controlling the directional arrangement of gray cast iron solidification structure by magnetic field. Background Art

[0002] Steel and cast iron are collectively referred to as Fe-C alloys. As an important engineering structural material, they are consumed in huge quantities every year and play an irreplaceable role in modern industry. It is well known that the mechanical properties of alloys can be effectively improved by regulating factors such as the morphology, transformation amount, and size distribution of the microstructure. In addition, the allotropic transformation of Fe and the ability to form carbides provide a rich microstructure for the solid-state phase transformation of Fe-C alloys. In particular, the process of transformation from FCC-austenite (γ) to BCC-ferrite (α) has attracted widespread attention from researchers because it is the basis for other phase transformations (such as bainite and martensite) occurring at low temperatures. The transformation from austenite to ferrite is one of the main issues in controlling the final microstructure, so it is crucial to achieve microstructure regulation in this process. Summary of the invention

[0003] The purpose of the present invention is to provide a gray cast iron with a directional arrangement of solidification structure and a method for directional arrangement of gray cast iron solidification structure under a magnetic field. The directional arrangement of gray cast iron solidification structure provided by the present invention provides a new path for the development of high-performance gray cast iron preparation technology.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for regulating the directional arrangement of gray cast iron solidification structure by magnetic field, comprising the following steps:

[0006] The directional solidification device is placed in a magnet to ensure that the solid-liquid interface of the solidified sample is located in the central area of ​​the steady magnetic field and the direction of the magnetic field is parallel to the solidification direction; the gray cast iron sample is placed in the directional solidification device for melting and directionally solidification in sequence; the melting and directionally solidification are both carried out under the condition of applying a magnetic field; the growth rate of the directional solidification is 0.5 to 3 μm / s; and the magnetic field strength is below 12 T.

[0007] Preferably, the grey cast iron sample is a cylindrical sample rod with a diameter of 3 mm and a height of 120 mm.

[0008] Preferably, the intensity of the magnetic field is 4-12T.

[0009] Preferably, the strength of the magnetic field is 4T, 8T or 12T.

[0010] Preferably, the growth rate is 0.5 μm / s, 1 μm / s, 2 μm / s or 3 μm / s.

[0011] Preferably, the melting temperature is above 1450° C., and the holding time is 30 to 60 minutes.

[0012] The present invention provides a gray cast iron with a directional arrangement of solidification structure, which is obtained by the method described in the above scheme, and comprises eutectoid ferrite and flake graphite; the flake graphite is arranged parallel to the direction of the magnetic field; the grains of the eutectoid ferrite are distributed in an elongated shape parallel to the direction of the magnetic field, and the grains of the eutectoid ferrite are parallel to the direction of the magnetic field. <001> The texture components are enhanced.

[0013] The invention provides a method for regulating the directional arrangement of gray cast iron solidification structure by magnetic field, comprising the following steps: placing a directional solidification device in a magnet to ensure that the solid-liquid interface of the solidified sample is located in the central area of ​​a steady magnetic field; placing the gray cast iron sample in the directional solidification device to perform melting and directional solidification in sequence; the melting and directional solidification are both performed under the condition of applying a magnetic field; the growth rate of the directional solidification is 0.5-3 μm / s; and the magnetic field intensity is below 12 T.

[0014] The present invention is based on the magnetocrystalline anisotropy of graphite and ferrite under the action of a magnetic field, and the interaction of magnetic dipoles in ferrite, so as to change the directional solidification structure of gray cast iron. Specifically, when graphite grows along the a-axis, it is in the form of flake graphite. Since graphite has a hexagonal crystal structure, the basal plane has a strong sp 2 There are weak van der Waals bonds along the c-axis, which causes the magnetic susceptibility of the a-axis to be greater than that of the c-axis. Under the action of a magnetic field, the a-axis of graphite is easier to turn to the direction of the magnetic field. Therefore, after directional solidification by a magnetic field, the flake graphite is regularly arranged parallel to the direction of the magnetic field. There are a large number of Fe atoms with atomic magnetic moments in ferrite, which can be regarded as magnetic dipoles. These magnetic dipoles are randomly distributed under non-magnetic conditions. Once a magnetic field is applied, due to the interaction between the magnetic dipoles and the magnetic field, they tend to be arranged in an orderly manner parallel to the direction of the magnetic field, such as Figure 6 As shown. At the same time, based on the interaction between magnetic dipoles, adjacent magnetic dipoles perpendicular to the magnetic field direction repel each other, and on the contrary, two adjacent magnetic dipoles parallel to the magnetic field direction attract each other. Therefore, Fe atoms are easy to diffuse along the magnetic field direction to form elongated eutectoid ferrite grains and arrange along the magnetic field direction. In addition, the attraction between magnetic dipoles increases with the increase of magnetic field strength, making the eutectoid ferrite become more elongated with the increase of magnetic field strength. In addition, due to the magnetocrystalline anisotropy of ferrite, its easy magnetization axis is <001> crystal direction, so under the action of magnetic field, eutectoid ferrite <001> The driving force for nucleation and growth in the crystal direction is the largest, and this driving force increases with the increase of magnetic field strength, resulting in the formation of <001> The texture components increase with the increase of magnetic field intensity.

[0015] The present invention realizes the regulation of gray cast iron directional solidification structure through magnetic field assisted directional solidification technology, solves the problem that other methods cannot achieve directional arrangement of gray cast iron solidification structure, and provides a new path for the development of high-performance gray cast iron preparation technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 EBSD characterization results of the eutectoid structure of the longitudinal section of directionally solidified gray cast iron at a growth rate of 1 μm / s under different magnetic field intensities; (a) to (d) correspond to magnetic field intensities of 0T, 4T, 8T, and 12T, respectively; (a1) to (d1) are orientation images of eutectoid ferrite grains; (a2) to (d2) are anti-pole figures of the texture parallel to the magnetic field direction;

[0017] Figure 2 EBSD characterization results of the eutectoid structure of the longitudinal section of directionally solidified gray cast iron at a growth rate of 2 μm / s under different magnetic field intensities; (a) to (d) correspond to magnetic field intensities of 0T, 4T, 8T, and 12T, respectively; (a1) to (d1) are orientation images of eutectoid ferrite grains; (a2) to (d2) are anti-pole figures of the texture parallel to the magnetic field direction;

[0018] Figure 3 EBSD characterization results of the eutectoid structure of the longitudinal section of directionally solidified gray cast iron at a growth rate of 3μm / s under different magnetic field intensities; (a) to (d) correspond to magnetic field intensities of 0T, 4T, 8T, and 12T, respectively; (a1) to (d1) are orientation images of eutectoid ferrite grains; (a2) to (d2) are anti-pole figures of the texture parallel to the magnetic field direction;

[0019] Figure 4 XRD patterns of the eutectoid structure of directionally solidified gray cast iron cross section at a growth rate of 1 μm / s under different magnetic field intensities;

[0020] Figure 5 Schematic diagram of directional solidification device under magnetic field (a) and magnetic field intensity distribution diagram (b);

[0021] Figure 6 Schematic diagram of the distribution of magnetic dipoles in eutectoid ferrite, (a) no magnetic field; (b) applied magnetic field. DETAILED DESCRIPTION

[0022] The present invention provides a method for regulating the directional arrangement of gray cast iron solidification structure by magnetic field, comprising the following steps:

[0023] The directional solidification device is placed in a magnet to ensure that the solid-liquid interface of the solidified sample is located in the central area of ​​the steady magnetic field and the direction of the magnetic field is parallel to the solidification direction; the gray cast iron sample is placed in the directional solidification device for melting and directionally solidification in sequence; the melting and directionally solidification are both carried out under the condition of applying a magnetic field; the growth rate of the directional solidification is 0.5 to 3 μm / s; and the magnetic field strength is below 12 T.

[0024] The present invention has no special requirements for the directional solidification equipment, and any directional solidification equipment known in the art can be used. Figure 5 As shown, the present invention places the directional solidification device in a magnet to ensure that the solid-liquid interface of the solidified sample is located in the central area of ​​the steady magnetic field. In the present invention, the intensity distribution of the magnetic field is as follows: Figure 5 As shown in (b), the sample begins to solidify below the solid-liquid interface, and only the central area is a steady magnetic field area. The present invention locates the solid-liquid interface of the solidified sample in the central area of ​​the steady magnetic field to ensure that the magnetic field to which the sample is subjected during solidification matches the target intensity.

[0025] The present invention has no special requirements for the gray cast iron sample, and any gray cast iron known in the art can be used. In the present invention, the chemical composition (wt.%) of the gray cast iron sample is: C: 3.82; Si: 2.13; Mn: 0.37; S: 0.004; P: 0.039; Mg: 0.032; Fe: balance. In the present invention, the gray cast iron sample is preferably a cylindrical sample rod with a diameter of 3 mm and a height of 120 mm. The present invention preferably first grinds the gray cast iron sample with sandpaper to remove the surface oxide layer, and then ultrasonically cleans and dries the grinded sample with alcohol and places it in a corundum tube for melting. The present invention grinds the gray cast iron sample so that the directional solidification sample maintains the stability of the composition, and further avoids the generation of bubbles on the surface of the directional solidification sample.

[0026] In the present invention, the melting temperature is preferably above 1450°C, more preferably 1450-1550°C; the holding time is preferably 30-60 minutes. The present invention preferably melts under a protective atmosphere, and the protective atmosphere is preferably argon. The present invention preferably fixes the corundum tube containing the gray cast iron sample to the top of the pull rod by high-temperature glue, slowly pushes it into the heating furnace, then closes the equipment, circulates the protective gas, starts the regulated DC power supply, heats to the melting temperature (the heating rate is controlled within 10°C / min), starts the magnetic field device during the holding stage, sets the required magnetic field strength, and after holding for 30-60 minutes, starts the servo pulling system for directional solidification.

[0027] In the present invention, the magnetic field strength is preferably below 12 T, more preferably 4 to 12 T, and in the embodiments of the present invention, specifically 4 T, 8 T or 12 T. In the present invention, the growth rate of the directional solidification is 0.5 to 3 μm / s, preferably 0.5 μm / s, 1 μm / s, 2 μm / s or 3 μm / s. In the present invention, when the growth rate exceeds the above range, the effect of tissue directional arrangement under the magnetic field will be weakened.

[0028] In the present invention, the gray cast iron undergoes eutectic transformation (liquid phase→graphite+austenite) and eutectoid transformation (austenite→graphite+eutectoid ferrite) during directional solidification, and finally the directional solidification structure of the present invention is the eutectoid zone structure of the stable growth zone.

[0029] In the present invention, the gray cast iron sample prepared by the magnetic field-assisted directional solidification technology can be divided into three regions, the upper half is the liquid phase region, the middle is the eutectic region, and the lower half is the stable growth solid phase region, that is, the eutectoid region (eutectoid structure composed of graphite + eutectoid ferrite). In the absence of a magnetic field, the flake graphite is randomly distributed, and the application of a magnetic field causes the flake graphite to be oriented parallel to the direction of the magnetic field. In the absence of a magnetic field, the morphology of the eutectoid ferrite is equiaxed and has no specific orientation. The application of a magnetic field causes the eutectoid ferrite to be transformed into slender grains oriented parallel to the direction of the magnetic field, and <001> The texture components are enhanced.

[0030] In the present invention, in order to facilitate the subsequent observation of the organizational morphology of each zone, the present invention preferably waits for the gray cast iron sample to be pulled to a length of 60 mm and then the sample is pulled to a length of 10 4 μm / s and quickly pulled into a cooling pool filled with liquid Ga-In-Sn for quenching experiments. Finally, turn off the power, wait for the directional solidification device to cool down, and take out the sample when it cools to room temperature. Cut a 15mm long cylinder 5mm above and 10mm below the solid-solid interface of the sample (eutectic-eutectoid interface when eutectoid transformation occurs), cut it axially, and take a 5mm high cylinder 10mm below the solid-solid interface (the longitudinal section is used for EBSD analysis to observe the arrangement of the graphite and eutectoid ferrite microstructures along the magnetic field direction, and the crystal orientation distribution of eutectoid ferrite, and the cross section is used for XRD analysis of the crystal orientation changes of graphite). The obtained samples were cold mounted with epoxy resin, mechanically ground and polished for subsequent structural characterization and analysis.

[0031] Subsequently, the cross-sectional samples were characterized by X-ray diffractometer to characterize the changes in graphite crystal orientation under different magnetic field strengths. The longitudinal cross-sectional samples were observed by electron backscatter diffractometer to observe the morphology and texture evolution of flake graphite and ferrite.

[0032] The present invention provides gray cast iron with directional solidification structure obtained by the method of the above scheme, comprising eutectoid ferrite and flake graphite; the flake graphite is arranged parallel to the magnetic field direction; the grains of the eutectoid ferrite are distributed in an elongated shape parallel to the magnetic field direction, and the grains of the eutectoid ferrite are parallel to the magnetic field direction. <001> The texture components are enhanced.

[0033] The method for regulating the directional arrangement of the solidification structure of grey cast iron by using a magnetic field provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0034] Example 1

[0035] The experimental raw material selected in this embodiment is industrial gray cast iron, and its chemical composition (wt.%) is as follows: C: 3.82; Si: 2.13; Mn: 0.37; S: 0.004; P: 0.039; Mg: 0.032; Fe: Bal. A sample rod with a diameter of 3 mm and a length of 150 mm was cut from the gray cast iron ingot using electric spark wire cutting technology. The sample rod was polished with sandpaper, ultrasonically cleaned and dried with alcohol, and then loaded into a clean corundum tube. The operation process of the directional solidification experiment under a magnetic field is as follows: the corundum tube containing the sample is pushed into the heating furnace and heated to a preset temperature of 1500°C. The magnetic field device is turned on at the beginning of the insulation stage, and the magnetic field strength is set to 0T, 4T, 8T, and 12T respectively. After insulation for 30 minutes, the servo pulling system is turned on, and the pulling distance is set to 60mm and the growth rate is 1μm / s; when the sample has grown stably to a length of 60mm, the sample is pulled at 10 4 μm / s and pulled into a cooling pool filled with liquid Ga-In-Sn for quenching experiments to obtain the required directional solidification samples. Take out the samples when cooled to room temperature. Cut a 15mm long cylinder 5mm above and 10mm below the solid-solid interface of the sample, cut it axially, and take a 5mm high cylinder 10mm below the solid-solid interface. All the samples obtained were cold mounted with epoxy resin, mechanically ground and polished.

[0036] The cross-section samples were mechanically ground and polished, and then electropolished using a LectroPol-5 electropolisher (Struers) with an electrolyte of 10 vol.% HClO 4 +90vol.%C 2 H 5OH, voltage of 25 V, time of 10 s, and then the change of graphite crystal orientation under different magnetic field strengths was characterized by X-ray diffractometer. The longitudinal section samples were ground and polished, and then vibrated and polished using VibroMet 2 vibratory polisher (Buehler). The polishing liquid was alumina suspension, and the vibratory polishing time was 6 h. Then the morphology and texture evolution of graphite and ferrite were observed by Hikari XPII electron backscatter diffractometer (EDAX).

[0037] The experimental results of this example can be found in Figure 1 It can be found that with the increase of magnetic field intensity, the morphology of eutectoid ferrite in the directionally solidified gray cast iron sample changes from equiaxed grains in the absence of magnetic field to elongated grains parallel to the magnetic field direction, and the <001> The texture component is enhanced, and the flake graphite is oriented parallel to the magnetic field direction. Figure 4 The XRD results show that as the magnetic field intensity increases, the The peak value of the crystal face increases, which can be inferred from the graphite The crystal orientation is parallel to the magnetic field direction, which in turn causes the flake graphite to be oriented parallel to the magnetic field direction.

[0038] Example 2

[0039] The process and steps of this embodiment are basically the same as those of the above-mentioned embodiment 1. The only difference is that the growth rate of the directional solidification sample is 2 μm / s. Figure 2 It can also be found that as the magnetic field intensity increases, the flake graphite is oriented parallel to the magnetic field direction, and the morphology of the eutectoid ferrite changes from the equiaxed shape when there is no magnetic field to the elongated grains parallel to the magnetic field direction. <001> The texture components are enhanced.

[0040] Example 3

[0041] The process and steps of this embodiment are basically the same as those of the above-mentioned embodiment 1. The difference is that the growth rate of the directional solidification sample is 3 μm / s. Figure 3 Obviously, when there is no magnetic field, the morphology of eutectoid ferrite is mostly equiaxed. As the magnetic field strength increases, the eutectoid ferrite stretches parallel to the magnetic field. Similarly, it can be observed that as the magnetic field strength increases, the flake graphite is oriented parallel to the magnetic field, and the eutectoid ferrite is parallel to the magnetic field. <001> The texture components are enhanced, which is consistent with the law of directionally solidified gray cast iron with growth rates of 1μm / s and 2μm / s under different magnetic field intensities.

[0042] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for regulating the directional arrangement of gray cast iron solidification structure by magnetic field, characterized in that: The following steps are involved: The directional solidification device is placed in a magnet to ensure that the solid-liquid interface of the solidified sample is located in the central area of ​​the steady magnetic field and the direction of the magnetic field is parallel to the solidification direction; the gray cast iron sample is placed in the directional solidification device for melting and directionally solidification in sequence; the melting and directionally solidification are both carried out under the condition of applying a magnetic field; the growth rate of the directional solidification is 0.5 to 3 μm / s; and the magnetic field strength is 4 to 8 T.

2. The method according to claim 1, characterized in that: The grey cast iron sample is a cylindrical sample rod with a diameter of 3 mm and a height of 120 mm.

3. The method according to claim 1, characterized in that The growth rate is 0.5 μm / s, 1 μm / s, 2 μm / s or 3 μm / s.

4. The method according to claim 1, characterized in that: The melting temperature is above 1450° C., and the heat preservation time is 30 to 60 minutes.

5. A gray cast iron with a directional solidification structure, obtained by the method according to any one of claims 1 to 4, comprising eutectoid ferrite and flake graphite; the flake graphite is arranged parallel to the magnetic field; the grains of the eutectoid ferrite are distributed in an elongated shape parallel to the magnetic field, and the grains parallel to the magnetic field are arranged parallel to the magnetic field. <001> The texture components are enhanced.

Citation Information

Patent Citations

  • Axially oriented directional solidification process in magnetic field

    CN1740370A